Arboreal Entomophagous Arthropods of Rice Insect Pests Inhabiting Adaptive Vegetables and Refugia in Freshwater Swamps of South Sumatra - Karenina, Tili; Herlinda, Siti; Irsan, Chandra; Pujiastuti, Yulia (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
The plants surrounding rice field serve as a habitat and niche for entomophagous arthropods. This study aimed to identify the entomophagous arthropod species and to analyze their abundance and community in vegetables and refugia grown in the rice field. The field was surrounded by 4 species of refugia (Zinnia sp., Tagetes erecta, Cosmos caudatus, and Sesamum indicum) and 4 species of vegetables (Vigna unguiculata, Momordica charantia, Cucumis sativus, and Luffa acutangula). The arthropod found were 67 species of predatory arthropods and 22 species of parasitoids. The predatory arthropods were mostly found in rice (51 species) followed by Zinnia sp. (15 species), and M. charantia (9 species). Parasitoid species were dominantly found in rice (19 species), Zinnia sp. (7 species), and M. charantia (6 species). The predatory arthropods mostly found were Tetragnatha javana, Tetragnatha virescens, and Paederus fuscipes, while the dominant parasitoids were Cardiochiles sp., Elasmus sp., and Snellenius sp. The parasitoid species composition in rice was more similar to those in bitter melon and zinnia. The composition of predatory arthropod species in rice was similar to those in all vegetables and refugia, except in cowpea. Zinnia sp. and M. charantia were the most chosen habitat by entomophagous arthropods.